Married women and the law in premodern northwest Europe / edited by Cordelia Beattie and Matthew Frank Stevens. - Beattie, Cordelia; Stevens, Matthew Frank (Boydell & Brewer, 2013)
There has been a tendency in scholarship on premodern women and the law to see married women as hidden from view, obscured by their husbands in legal records. This volume provides a corrective view, arguing that the extent to which the legal principle of 'coverture' applied has been over-emphasized. In particular, it points up differences between the English common law position, which gave husbands guardianship over their wives and their wives' property, and the position elsewhere in northwest Europe, where wives' property became part of a community of property. Detailed studies of legal material from medieval and early modern England, Wales, Scotland, Ireland, Ghent, Sweden, Norway and Germany enable a better sense of how, when, and where the legal principle of 'coverture' was applied and what effect this had on the lives of married women. Key threads running through the book are married women's rights regarding the possession of moveable and immovable property, marital property at the dissolution of marriage, married women's capacity to act as agents of their husbands and households in transacting business, and married women's interactions with the courts. Cordelia Beattie is Senior Lecturer in Medieval History at the University of Edinburgh; Matthew Frank Stevens is Lecturer in Medieval History at Swansea University. Contributors: Lars Ivar Hansen, Shennan Hutton, Lizabeth Johnson, Gillian Kenny, Mia Korpiola, Miriam Muller, S. C. Ogilvie, Alexandra Shepard, Cathryn Spence.